Analysis of the behavior and performance of the short link eccentric brace frame type multistory x-brace with variable link length and L / H ratio - Aseanto Resi (Journal of World Conference (JWC), 2021)
In the process of planning earthquake-resistant building structures, steel structures are still an option. This is because steel material has relatively high load resistance and elastic properties of steel which contribute to better ductility and energy dissipation than concrete. Eccentric Brace Frame System (SRBE) is a lateral load bearing system that has good strength, stiffness and ductility. In this study, the SRBE Short Link Multistory X-bracing type structure with variable link length and L / H ratio was evaluated using pushover analysis to determine the structure's behavior and performance in terms of stiffness, strength and ductility of the structure. The analysis was conducted on 9 10-story building models with different link lengths and L / H ratio. From the results of the comparative analysis of each structural model, it is found that the C2 model with a link length of 900 mm and an L / H ratio of 1.5 has a stiffer structure. Model C3 with a link length of 900 mm and a ratio of L / H = 1.75 has a greater strength to withstand earthquake loads. The use of a link length of 300 mm and an L / H ratio = 1.5 results in an increasingly ductile structure. The results of the structural performance are at the Immidiate Occupancy level, but there are several models with one of the X or Y load directions that have a Life Safety structural performance level. The use of a link length of 300 mm and an L / H ratio = 1.5 results in an increasingly ductile structure. The results of the structural performance are at the Immidiate Occupancy level, but there are several models with one of the X or Y load directions that have a Life Safety structural performance level. The use of a link length of 300 mm and an L / H ratio = 1.5 results in an increasingly ductile structure. The results of the structural performance are at the Immidiate Occupancy level, but there are several models with one of the X or Y load directions that have a Life Safety structural performance level.